Adolescent pregnant women experiences in three primary health care centers of Yogyakarta: the need of friendly and sensitive support care - Dara Ardhia; Budi Wahyuni; Wenny Artanty Nisman (Berita Kedokteran Masyarakat (BKM), 2018)
Purpose: Explore the meaning of adolescent’s experience and social support needs from health staff in pregnancy.Method: This research was a qualitative research with phenomenology. The study was conducted in three catchment areas of Puskesmas Jetis, Gedongtengen and Umbulharjo 1 from 6 May to 7 July 2017. The selection of participants using the technique of maximal variation and the number of participants adjusted to the varied place of study and the variation of participants and the number of participants was 6. The research data was collected by using in-depth interview technique with semi-structured interview guide. The data were analyzed with Collaizi technique analysis.Results: There are 5 themes in this study that is, the experience of adolescents at the beginning of their pregnancies, differences in the reasons adolescent maintain their pregnancies, the form of support that adolescent have gained during pregnancy, adolescent perspectives on the behavior of health staff during accompanying pregnancy and social support needs of adolescent pregnancy from health staff .Conclusion: Adolescent acceptance of pregnancy occurs as pregnancy progresses, support from optimal health staff increases teen motivation to maintain and run pregnancy well and informational support from health staff is a key requirement for teenage pregnancy.